Solvent-free sonochemistry: Sonochemical organic synthesis in the absence of a liquid medium - Crawford, Deborah E. (Beilstein Journal of Organic Chemistry, 2017)
Sonochemistry, i.e., the application of mechanical energy in the form of sound waves, has recently been recognised for its similarity to mechanochemistry and is now included under the umbrella term of mechanochemistry. Typically, due to the hypothesised cavitation mechanism, a liquid medium is considered as a necessity for a process to take place as a result of ultrasonic irradiation. In view of this, condensation reactions between solid reagents in the complete absence of solvent were carried out successfully by ultrasonic irradiation with the importance of particle size being highlighted. This work increases the potential of sonochemistry in the drive towards a sustainable future.
Keywords: mechanochemistry; organic; solvent-free; sonochemistry; synthesis

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Kaupp, G. (CrystEngComm, 2009)

(untitled) - Rivas, D. F.; Cintas, P.; Gardeniers, H. J. G. E. (Chem. Commun., 2012)

(untitled) - Crawford, D. E.; Casaban, J.; Haydon, R.; Giri, N.; McNally, T.; James, S. L. (Chem. Sci., 2015)

(untitled) - Crawford, D. E.; Wright, L. A.; James, S. L.; Abbott, A. P. (Chem. Commun., 2016)

(untitled) - Crawford, D. E.; Miskimmin, C. K. G.; Albadarin, A. B.; Walker, G.; James, S. L. (Green Chem., 2017)

(untitled) - Suslick, K. S. (Faraday Discuss., 2014)

(untitled) - Margulis, M. A. (Ultrason. Sonochem., 1994)

(untitled) - Tanaka, R.; Takahashi, N.; Nakamura, Y.; Hattori, Y.; Ashizawa, K.; Otsuka, M. (RSC Adv., 2016)

(untitled) - Notley, S. M. (Langmuir, 2012)

(untitled) - Suslick, K. S. (Adv. Organomet. Chem., 1986)

(untitled) - Li, J.-T.; Wang, S.-X.; Chen, G.-F.; Li, T.-S. (Curr. Org. Synth., 2005)

(untitled) - Jamali, M. K.; Kazi, T. G.; Arain, M. B.; Afridi, H. I.; Jalbani, N.; Memon, A. R. (J. Agron. Crop Sci., 2007)

(untitled) - Wen-Chou, L.; Maltsev, A. N.; Kobosev, N. I. (Russ. J. Phys. Chem., 1964)

(untitled) - Maltsev, A. N. (Russ. J. Phys. Chem., 1976)

(untitled) - Kowalska, E.; Dziegielewska, M. (Ultrasonics, 1976)

(untitled) - Doan, T. L. H.; Le, T. N. (Synth. Commun., 2012)

(untitled) - Li, J.-T.; Li, T.-S.; Li, L.-J.; Cheng, X. (Ultrason. Sonochem., 1999)

(untitled) - Li, J.-T.; Cui, Y.; Chen, G.-F.; Cheng, Z.-L.; Li, T.-S. (Synth. Commun., 2003)

(untitled) - Yadav, J. S.; Reddy, B. V. S.; Reddy, K. B.; Raj, K. R.; Prasad, A. R. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Ali, M. M.; Sana, S.; Tasneem; Rajanna, K. C.; Saiprakash, P. K. (Synth. Commun., 2002)

(untitled) - Rieke, R. D.; Kim, S.-H. (J. Org. Chem., 1998)